Cold Chain Optimization in the Food Industry: Integration of IoT-Based Monitoring and Modified Atmosphere Packaging Using High-Barrier Mono-Material - Nurhayati Nurhayati; Felycia Angellia; Jolie Verlita; Malvin Widyanto Tjoa; Felicia Novia Alverina; Made Grazielle (Indonesian Journal Publisher, 2026)
This study evaluates the integration of Internet of Things (IoT)-based temperature monitoring and high-barrier mono-material Modified Atmosphere Packaging (MAP) as a strategy to reduce food loss in cold chain systems. The research assesses the technical, environmental, and economic implications of implementing real-time temperature control alongside recyclable packaging materials. The results indicate that IoT-based monitoring reduces spoilage by enabling rapid detection of temperature deviations and corrective actions during storage and transportation. In parallel, high-barrier mono-material MAP maintains internal gas composition, extending shelf life and stabilizing product quality throughout distribution. Life cycle and techno-economic considerations suggest that although initial investment and material costs may increase, reductions in food loss and improved sell-through can offset expenses, particularly for high-value perishable products. Overall, the integration of digital monitoring and barrier packaging provides a preventive and preservative approach that enhances cold chain performance, reduces waste, and supports environmental sustainability.